2018
DOI: 10.1111/bph.14177
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of two novel transient receptor potential melastatin 8 antagonists in acute and chronic pain models in rat

Abstract: Our findings, in agreement with previous literature, encourage further studies for a better comprehension of the therapeutic potential of TRPM8 blockers as novel agents for pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 66 publications
(79 reference statements)
4
51
1
Order By: Relevance
“…However, cold stimulation was not examined by our team, which is likely the key modality to evaluate for this mechanism (Patel et al 2014). In contrast, other teams have reported that TRPM8 receptor antagonists were efficacious against mechanical allodynia in rodent models (De Caro et al 2018;Salat and Filipek 2015), but it is unclear how this effect was induced since these studies did not determine the pathways/sites that were modulated by the antagonists.…”
Section: Discussionmentioning
confidence: 92%
“…However, cold stimulation was not examined by our team, which is likely the key modality to evaluate for this mechanism (Patel et al 2014). In contrast, other teams have reported that TRPM8 receptor antagonists were efficacious against mechanical allodynia in rodent models (De Caro et al 2018;Salat and Filipek 2015), but it is unclear how this effect was induced since these studies did not determine the pathways/sites that were modulated by the antagonists.…”
Section: Discussionmentioning
confidence: 92%
“… 99 It has been reported that TRPM8 activation produces analgesia, 73 but TRPM8 inhibition has also been found crucial to reduce acute and chronic pain. 16 , 17 Effect of the variants on the functional properties of the TRPM8 channel are not known, and thus their contribution to the pain phenotype in the 2 carriers awaits further studies. Expanding understanding of TRP channels involved in ocular itch and pain 48 and of how injury and inflammation can induce changes in ocular pain pathways 5 likely add to our understanding of CN in the future.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM8 has a role in core body temperature regulation and detection of TRM8 antagonist underline its competence in paintreatment [17,42]. A pharmacological blockage of TRPM8 signaling determines a reduction in cold hypersensitivity induced by nerve injury [6,15,43].…”
Section: Discussionmentioning
confidence: 99%